Development without the tears - Abd Razak, Dzulkifli (2006)
We don’t love our rivers. And we fell our trees, clear our jungles and level hills. Malaysians had better pay heed or they will have to pay for all the uncaring development. SUCH is its importance that no less than the president of Indonesia saw it fit to talk about it at the 50th anniversary of the Association of Southeast Asian Institutes of Higher Learning early this month. The president, in his address at Istana Merdeka in Jakarta, dealt passionately with the conference topic which was, "Disaster Management through Regional Cooperation". For someone who is responsible for hundreds of millions vulnerable to disasters, Susilo Bambang Yudhoyono himself had been faced natural disasters several times since assuming the presidency not too long ago.